Mycosis Fungoides - Singh Shri Nath; Bhattamishra Asit Baran; Keki Gardin Homyar (Wolters Kluwer Medknow Publications, 1999)
A fifty six year old patient developed erythematcus macules, papules, annular plaques, nodules, tumours, ulcerated lesions and poikiloderma. After initial difficulty, a diagnosis of mycosis fungoides was finally made on histopathology.